Kinesin‐1 inhibits the aggregation of amyloid‐β peptide as detected by fluorescence cross‐correlation spectroscopy. Issue 7 (29th March 2016) - Zheng, Yanpeng; Tian, Shijun; Peng, Xianglei; Yang, Jingfa; Fu, Yuanhui; Jiao, Yueying; Zhao, Jiang; He, Jinsheng; Hong, Tao
Abstract : Although the exact etiology and pathogenesis of Alzheimer's disease (AD) are still unclear, amyloid‐β (Aβ) generated by the proteolytic processing of amyloid‐β precursor protein (APP) aggregate to form toxic amyloid species. Kinesin‐1 is the first identified ATP‐dependent axonal transport motor protein that has been proven to affect Aβ generation and deposition. In this paper, we applied dual‐color fluorescence cross‐correlation spectroscopy (DC‐FCCS) to investigate the direct interaction of Aβ with kinesin‐1 at the single‐molecule fluorescence level in vitro . The results showed that two kinds of enhanced green fluorescent protein (EGFP)‐tagged kinesin light‐chain subunits of kinesin‐1(KLCs), KLC‐E and E‐KLC inhibited the aggregation of Aβ over a period of time, providing additional insight into the mechanism of axonal transport deficits in AD. Abstract :